Targeting endogenous proteins for degradation through the affinity-directed protein missile system - Luke J. Fulcher (Open Biology, 2017)
Targeted proteolysis of endogenous proteins is desirable as a research toolkit and in therapeutics. CRISPR/Cas9-mediated gene knockouts are irreversible and often not feasible for many genes. Similarly, RNA interference approaches necessitate prolonged treatments, can lead to incomplete knockdowns and are often associated with off-target effects. Targeted proteolysis can overcome these limitations. In this report, we describe an affinity-directed protein missile (AdPROM) system that harbours the von Hippel–Lindau (VHL) protein, the substrate receptor of the Cullin2 (CUL2) E3 ligase complex, tethered to polypeptide binders that selectively bind and recruit endogenous target proteins to the CUL2-E3 ligase complex for ubiquitination and proteasomal degradation. By using synthetic monobodies that selectively bind the protein tyrosine phosphatase SHP2 and a camelid-derived VHH nanobody that selectively binds the human ASC protein, we demonstrate highly efficient AdPROM-mediated degradation of endogenous SHP2 and ASC in human cell lines. We show that AdPROM-mediated loss of SHP2 in cells impacts SHP2 biology. This study demonstrates for the first time that small polypeptide binders that selectively recognize endogenous target proteins can be exploited for AdPROM-mediated destruction of the target proteins.